Percutaneous absorption of vanilloids: in vivo and in vitro studies - Kasting, G B; Francis, W R; Bowman, L A; Kinnett, G O (Journal of pharmaceutical sciences, 1997)
The percutaneous absorption of three highly lipophilic analogs of capsaicin--vanillylnonanamide (VN), olvanil, and NE-21610--was measured in vivo in the CD:VAF rat, and in vitro through excised CD: VAF and SkH:Fz rat skin and human cadaver skin. Absorption and skin metabolism were monitored by radiolabel techniques. The rank order of penetration in all species was VN > olvanil > NE-21610, in accordance with that expected from their physical properties. Rat skin was more permeable than human skin by factors ranging from 4 to 8 for VN, 10 to 20 for olvanil, and approximately 10 to 100 for NE-21610. All three compounds were extensively metabolized during passage through fresh SkH:Fz rat skin, with the primary route of degradation for at least two of the compounds involving hydrolysis of the amide bond (the metabolites of NE-21610 were not identified). For the in vitro studies a range of receptor solutions was employed to determine a set of conditions that best mimicked in vivo absorption. The results with phosphate-buffered saline containing a preservative and 1-6% polyoxyethylene-20 oleyl ether (Oleth-20) were in good agreement with in vivo results for all three compounds for periods up to 24 h post-dose; after this time, in vivo absorption rates declined but in vitro rates remained relatively constant. Buffered saline or saline containing 0.5% bovine serum albumin led to marked underestimates of in vivo penetration for olvanil and NE-21610, whereas a 1:1 ethanol: water solution led to gross overestimates of the in vivo absorption rates for all three compounds.